2020
DOI: 10.3390/jfb11010007
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Dioxide Particles to Tune Radiopacity of Dental Adhesives: Microstructural and Physico-Chemical Evaluation

Abstract: The insufficient radiopacity of dental adhesives applied under composite restorations makes the radiographic diagnosis of recurrent caries challenging. Consequently, the misdiagnosis may lead to unnecessary replacement of restorations. The aims of this study were to formulate experimental dental adhesives containing cerium dioxide (CeO 2 ) and investigate the effects of different loadings of CeO 2 on their radiopacity and degree of conversion for the first time. CeO 2 was characterized by X-ray diffraction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Another relevant aspect for sealers is the achievement of radiopacity to make possible the differentiation of the material from the adjacent anatomical structures [30]. ISO 6876:2012 establishes 3 mm of aluminum as the desired radiopacity value for materials to be used as endodontic sealers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect for sealers is the achievement of radiopacity to make possible the differentiation of the material from the adjacent anatomical structures [30]. ISO 6876:2012 establishes 3 mm of aluminum as the desired radiopacity value for materials to be used as endodontic sealers.…”
Section: Discussionmentioning
confidence: 99%
“…An aluminum step-wedge was exposed simultaneously with the samples in all images. The aluminum step-wedge thickness ranged from 0.5 to 5.0 mm in increments of 0.5 mm [30]. The aluminum alloy used was Al 99.12, Fe 0.47, Mg 0.41, and with <0.1 of Cu (wt.%).…”
Section: Water Sorption and Solubilitymentioning
confidence: 99%
“…Ceria-containing polymer composites could be useful for various implants and medical devices (including hearing aids and orthodontic and orthopedic products, etc.). For instance, CeNPs have been shown to protect human dental stem cells from oxidative insult [ 136 ] and have been used as a filler to tune the radiopacity of dental polymeric adhesive (methacrylate resin) to meet the requirement of ISO 4049 [ 137 ]: the results obtained have shown that CeO 2 at 4.32 vol.% exceeds the radiopacity threshold value. CeNPs have also demonstrated antibacterial activity against dental bacteria (including Streptococcus mutans [ 138 ]) responsible for cariogenic processes.…”
Section: Other Biomedical Applications and Future Trends Of Cenps-mentioning
confidence: 99%
“…Inorganic fillers have been incorporated into dental adhesives aiming to reduce polymeric degradation via increasing hydrolytic stability (Münchow and Bottino, 2017). Furthermore, these particles have been tuning in adhesives formulation to improve polymers' radiopacity (Garcia et al, 2020a) and mechanical properties (Lohbauer et al, 2010;Belli et al, 2014). Inorganic fillers have also been proposed to improve the therapeutic activity of resin-based materials.…”
Section: Introductionmentioning
confidence: 99%